Impact of reduced sonic boom exposure on introspective judgments and annoyance, pleasantness and loudness ratings for simulated booms presented in a realistic indoor environment - Marmel Frédéric; Cretagne Léo; Thuong Linh-Thao; Coulouvrat François; Fritz Claudia (Acta Acustica)
This paper reports on a project that quantified the effects of sonic boom exposure on human responses, in situations representative of the daily life of European citizens, to inform policy, and develop protection concepts for a new generation of supersonic commercial aircraft that should emit a reduced but perceivable boom while flying overland. Two reduced boom simulators were affixed to the bedroom windows of a house located on our university campus. The simulators were used to study indoor the participants’ responses to simulated “outdoor” booms. Testing took place in both the living room and kitchen because the booms caused different intensities of rattle noise in those two rooms. Participants performed cognitive and psychophysical tasks (Marmel et al. Acta Acust. 8 (2024) 1. https://doi.org/10.1051/aacus/2023063) and had mandatory rests. Questionnaires were used to assess the participants’ introspective judgment of the boom interference with the activities and how it could be linked to their noise sensitivity. In addition, the participants’ perception of the booms was studied via ratings of annoyance and pleasantness, and via loudness comparisons. The negative interference of the booms was greater during rest than during tasks and for booms with higher than lower levels. This was not directly reflected in the objective performance degradation reported in the reference cited above and thus contributes to a more complete picture of the influence of the sonic booms on humans. Moreover, booms were found to be annoying and unpleasant, even more so at a higher level and with the presence of rattle noise.